Cover Picture: Heteronuclear NMR Spectroscopy as a Surface‐Selective Technique: A Unique Look at the Hydroxyl Groups of γ‐Alumina. (Chem. Eur. J. 14/2014). Issue 14 (1st April 2014) - Taoufik, Mostafa; Szeto, Kai C.; Merle, Nicolas; Rosal, Iker Del; Maron, Laurent; Trébosc, Julien; Tricot, Grégory; Gauvin, Régis M.; Delevoye, Laurent
<x xml:space="preserve">Abstract</x> The combination of high magnetic field and advanced 1H–27Al correlation solid‐state NMR techniques provides unprecedented data on the topology of the surface hydroxyl groups of γ‐alumina. For more details, see the Full Paper by R. M. Gauvin, L. Maron, M. Taoufik et al. on page 4038 ff. Photograph: Rock Islands, Palau, copyright: optionm – fotolia. com. We thank Matthieu Morin for his assistance with artwork.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>